PERBEDAAN PRESTASI BELAJAR PADA ANAK STUNTING DAN NON STUNTING DI SDN 03 DUPI KABUPATEN GORONTALO - Imran Tumenggung; Rika Syamsu (JOURNAL HEALTH AND NUTRITIONS, 2018)
ABSTRACT Until now stunting is one of the nutritional problems that needs attention. National stunting prevalence in 2013 was 37.2%, which means an increase compared to 2010 (35.6%). The prevalence of stunting in Gorontalo is 38.9% and is ranked 18th out of 20 provinces above national prevalence. This study aims to determine the differences in learning achievement in stunting and non-stunting children in Dulupi Elementary School 03, Dulupi District, Boalemo Regency. This study used analytic survey with a cross sectional study design. The population of all school children in Dulupi Elementary School 03 (grade 1 s.d grade 5) is 231 children. Data collection is done using observation sheets, data analysis using Chi square (X2) test. Based on the results of the study, it was found that children categorized as stunting had a good value of 20 people (62.5%), while non-stunting had a good score of 52 people (89.95%). The children with the most non-stunting nutritional status were as many as 58 children (64.4%), while the stunting were 32 people (35.5%). The statistical test p = 0.002 X2 (Chi square) of 9.504 was greater than X2 table 3.481, meaning Ho was rejected and Ha accepted. The conclusion of this study is that there are differences in learning achievement in stunting and non-stunting children in Dulupi Elementary School 03, Dulupi District, Boalemo Regency. ABSTRAK Sampai saat ini stunting merupakan salah satu masalah gizi yang perlu mendapat perhatian. Prevalensi stunting secara nasional tahun 2013 adalah 37,2%, yang berarti terjadi peningkatan dibandingkan tahun 2010 (35,6%). Prevalensi stunting di Gorontalo sebesar 38,9% berada diurutan ke 18 dari 20 provinsi di atas prevalensi nasional. Penelitian ini bertujuan untuk mengetahui perbedaan prestasi belajar pada anak stunting dan non stunting di SDN 03 Dulupi Kecamatan Dulupi Kabupaten Boalemo. Penelitian ini yang menggunakan survey analitik dengan rancangan cross sectional study. Populasi seluruh anak sekolah di SDN 03 Dulupi (kelas 1 s.d kelas 5) sebanyak 231 anak. Pengumpulan data dilakukan dengan menggunakan lembar observasi, analisis data menggunakan uji Chi square (X2). Berdasarkan hasil penelitian diperoleh bahwa anak yang dikategorikan stunting memiliki nilai yang baik sejumlah 20 orang (62,5%), sedangkan non stunting yang memiliki nilai baik sebanyak 52 orang (89,95%). Anak yang status gizinya non stunting paling banyak yaitu sebanyak 58 anak (64.4%), sedangkan yang stunting 32 orang (35.5 %).Uji statistik p = 0,002 X2 (Chi square) sebesar 9.504 lebih besar dari X2 tabel 3.481, artinya Ho ditolak dan Ha diterima. Kesimpulan penelitian ini adalah ada perbedaan prestasi belajar pada anak stunting dan non stunting di SDN 03 Dulupi Kecamatan Dulupi Kabupaten Boalemo.